2016
DOI: 10.1016/j.bjm.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of organic and conventionally grown fresh produce

Abstract: Fresh produce is a generalized term for a group of farm-produced crops, including fruits and vegetables. Organic agriculture has been on the rise and attracting the attention of the food production sector, since it uses eco-agricultural principles that are ostensibly environmentally-friendly and provides products potentially free from the residues of agrochemicals. Organic farming practices such as the use of animal manure can however increase the risk of contamination by enteric pathogenic microorganisms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 67 publications
1
56
0
2
Order By: Relevance
“…The median concentrations of filamentous fungi in examined vegetables were 3.49-5.0 log 10 CFU g -1 , being in the middle of values reported for fungi (moulds and yeasts) determined in the fresh and whole vegetables collected in various countries of the world, which varied within a fairly wide range of 1.1-6.1 log 10 CFU g -1 [2,3,12,13]. Concentrations of filamentous fungi in carrot and beetroot determined in the presented study were similar to the concentrations of aerobic mesophilic bacteria found in these vegetables on conventional farms [14].…”
Section: Levels Of Filamentous Fungi In Root Vegetables and Adjacent mentioning
confidence: 61%
See 1 more Smart Citation
“…The median concentrations of filamentous fungi in examined vegetables were 3.49-5.0 log 10 CFU g -1 , being in the middle of values reported for fungi (moulds and yeasts) determined in the fresh and whole vegetables collected in various countries of the world, which varied within a fairly wide range of 1.1-6.1 log 10 CFU g -1 [2,3,12,13]. Concentrations of filamentous fungi in carrot and beetroot determined in the presented study were similar to the concentrations of aerobic mesophilic bacteria found in these vegetables on conventional farms [14].…”
Section: Levels Of Filamentous Fungi In Root Vegetables and Adjacent mentioning
confidence: 61%
“…A great increase in vegetable consumption that has been observed globally in the past 20 years, is largely due to the fact that they provide health-promoting diet supplements, such as vitamins, minerals, antioxidants and fibres [1,2]. Organic farming that keeps to environmentally-friendly principles, without using artificial chemicals and genetic modifications, greatly contributes to the development of the vegetable branch of agriculture and is generally recognized as safe for consumers, in spite of some earlier reservations concerning the use of manure as a potential source of pathogenic microorganisms [2,3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In this system, harvest and packaging were manual operations with the marketable size lettuce packaged with intact root and peat moss plugs to help prolong shelf life. Although counts for all populations on both pre and postharvest lettuce leaves were within expectations for edible produce, packaging was associated with significantly higher counts (Warriner et al 2009;Cardamone et al 2015;Maffei et al 2016;Mahajan et al 2017;Merlini et al 2018). Packaging processes are believed to contribute to the transfer of microbes from plugs to leaves.…”
Section: Yeast and Mould (Ym)mentioning
confidence: 83%
“…In many parts of the world, organic cultivation systems use more manure than conventional growers, and chemical treatment against pathogens is prohibited in organic farming. There have thus been some assertions that organic produce represents a more significant safety risk than its non-organic counterpart, although, there is no unequivocal research evidence supporting this claim Loncarevic et al, 2005;Warriner et al, 2009;Ivey, 2011;Maffei et al, 2016).…”
Section: Introduction Of Pathogens Into Soil Via Manure/compost Applimentioning
confidence: 99%